Schizophrenia as a prodromal symptom in a patient harboring SNCA duplication. (April 2016) - Takamura, Shogo; Ikeda, Aya; Nishioka, Kenya; Furuya, Hirokazu; Tashiro, Mari; Matsushima, Takashi; Li, Yuanzhe; Yoshino, Hiroyo; Funayama, Manabu; Morinobu, Shigeru; Hattori, Nobutaka
Abstract: We present the case of a patient who developed delusions and auditory hallucinations and was clinically diagnosed as having schizophrenia. Ten years after the onset of schizophrenia, the disease progressed to mild parkinsonism. SNCA duplication was confirmed. This case expands the spectrum of clinical features in carriers of SNCA duplication.